Predictors of VA Primary Care Clerical Staff Burnout Using the Job Demands-Resources Model. Issue 4 (4th October 2022) - Medich, Melissa; Rose, Danielle; McClean, Michael; Nelson, Karin; Stewart, Gregory; Ganz, David A.; Yano, Elizabeth M.; Stockdale, Susan E.
Abstract : Primary care clerical staff may experience burnout if not adequately prepared and supported for patient-facing customer service tasks. Guided by the Job Demands-Resources (JD-R) model, we use national survey data from 707 primary care clerks at 349 VA clinics (2018; response rate: 12%) to evaluate associations between clerks' perceptions of tasks, work environment, training, and burnout. We found challenges with customer-facing tasks contribute to higher burnout, and supportive work environment was associated with lower burnout. Although perceptions of training were not associated with burnout, our results combined with the JD-R model suggest that customer service training may protect against burnout.